Federated Learning for Privacy-Preserving Employee Performance Analytics - Jay Barach (IEEE Access)
With the increasing sensitivity surrounding employee performance data, there is a pressing need for predictive systems that preserve privacy while delivering actionable insights to organizations. This paper introduces HFAN-Priv, a hierarchical federated attention network designed to predict employee resignation risk and evaluate performance trends without sharing raw data across organizations. The framework integrates feature-level and instance-level attention to model complex workforce patterns, applies differential privacy through gradient masking to ensure compliance with data protection regulations, and enhances interpretability using local SHAP and LIME explanations. Experiments conducted on a real-world employee productivity dataset show that HFAN-Priv achieves near-perfect predictive accuracy, robust cross-client generalization, and transparent decision-making, all while maintaining strong privacy guarantees. The proposed approach presents a scalable, ethical, and effective solution for HR analytics in decentralized environments.